Tumor treatment by pHLIP-targeted antigen delivery - DuPont, Michael; Visca, Hannah; Moshnikova, Anna; Engelman, Donald M.; Reshetnyak, Yana K.; Andreev, Oleg A. (Frontiers in Bioengineering and Biotechnology, 2023)
Targeted antigen delivery allows activation of the immune system to kill cancer cells. Here we report the targeted delivery of various epitopes, including a peptide, a small molecule, and a sugar, to tumors by pH Low Insertion Peptides (pHLIPs), which respond to surface acidity and insert to span the membranes of metabolically activated cancer and immune cells within tumors. Epitopes linked to the extracellular ends of pHLIP peptides were positioned at the surfaces of tumor cells and were recognized by corresponding anti-epitope antibodies. Special attention was devoted to the targeted delivery of the nine residue HA peptide epitope from the Flu virus hemagglutinin. The HA sequence is not present in the human genome, and immunity is readily developed during viral infection or immunization with KLH-HA supplemented with adjuvants. We tested and refined a series of double-headed HA-pHLIP agents, where two HA epitopes were linked to a single pHLIP peptide via two Peg12 or Peg24 polymers, which enable HA epitopes to engage both antibody binding sites. HA-epitopes positioned at the surfaces of tumor cells remain exposed to the extracellular space for 2448 hrs and are then internalized. Different vaccination schemes and various adjuvants, including analogs of FDA approved adjuvants, were tested in mice and resulted in a high titer of anti-HA antibodies. Anti-HA antibody binds HA-pHLIP in blood and travels as a complex leading to significant tumor targeting with no accumulation in organs and to hepatic clearance. HA-pHLIP agents induced regression of 4T1 triple negative breast tumor and B16F10 MHC-I negative melanoma tumors in immunized mice. The therapeutic efficacy potentially is limited by the drop of the level of anti-HA antibodies in the blood to background level after three injections of HA-pHLIP. We hypothesize that additional boosts would be required to keep a high titer of anti-HA antibodies to enhance efficacy. pHLIP-targeted antigen therapy may provide an opportunity to treat tumors unresponsive to T-cell based therapies, having a small number of neo-antigens, or deficient in MHC-I presentation at the surfaces of cancer cells either alone or in combination with other approaches.